Raspberry One - Ferry, Charles, 1927- (Boston : Houghton Mifflin, 1983)
Nick and Hildy, two young aircrewmen flying bombing support against Japan's kamikaze offensive in the Pacific, are devastated but ultimately strengthened by their war experience.
6.0
6.0
7-10.
Young Adult
Keywords: World War, 1939-1945 -- Pacific Ocean -- Juvenile fiction; Friendship -- Fiction; World War, 1939-1945 -- Aerial operations -- Fiction; World War, 1939-1945 -- Pacific Ocean -- Fiction; Friendship -- Fiction; World War, 1939-1945 -- Fiction